Production, quality and livestock carrying capacity of Panicum maximum and Sesbania grandiflora at saline soil with different manure application - Kusmiyati, F.; Pangestu, E.; Surahmanto, S.; Purbajanti, E.D.; Herwibawa, B. (Diponegoro University, 2019)
The objective of this study was to evaluate the effect of manure at saline soil on forage production, quality and livestock carrying capacity of P. maximum and S. grandiflora. The research was conducted on moderately saline soil at Rembang Regency, Central Java Province, Indonesia.Randomized complete block design was used as design experiment. The treatments were different dosage of manure as organic amendment (0, 10 and 20 tonnes/ha). Forage crops were P. maximum and S. grandiflora that planted monoculture or mixed-cropping. Parameters measured were dry matter (DM) production, ash, crude protein, crude fibre, ether extract, total digestible nutrients. P. maximum was cut eight times, S. grandiflora was cut six times during one year. The result showed that the highest total dry matter production of mixed cropping P. maximum and S. grandiflora was available at moderately saline soil with application 20 ton/ha manure. Total production of dry matter, crude protein and total digestible nutrient available at application 20 ton/ha manure were 29131 kg/ha/year; 3722 kg/ha/year and 17718 kg/ha/year, respectively. Carrying capacity based on dry matter, crude protein and total digestible nutrients were 10.8 AU/ha/year; 13.6 AU/ha/year and 11.3 AU/ha/year, respectively. In conclusion, application of 20 ton/ha manure at saline soil increased production, crude protein and carrying capacity.